2018
DOI: 10.3748/wjg.v24.i11.1259
|View full text |Cite
|
Sign up to set email alerts
|

Low-FODMAP vs regular rye bread in irritable bowel syndrome: Randomized SmartPill® study

Abstract: AIMTo compare the effects of regular vs low-FODMAP rye bread on irritable bowel syndrome (IBS) symptoms and to study gastrointestinal conditions with SmartPill®.METHODSOur aim was to evaluate if rye bread low in FODMAPs would cause reduced hydrogen excretion, lower intraluminal pressure, higher colonic pH, different transit times, and fewer IBS symptoms than regular rye bread. The study was a randomized, double-blind, controlled cross-over meal study. Female IBS patients (n = 7) ate study breads at three conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Another study has shown that low-FODMAPs rye breads, approximately 30% reduction of mannitol and fructans, caused less gastrointestinal symptoms, as abdominal pain, flatulence, stomach rum- and intestinal cramps ( Laatikainen et al, 2016 ). A third study conducted by Pirkola et al (2018) demonstrated that low-FODMAP rye bread leads to reduced colonic fermentation and flatulence severity when compared with regular rye bread consumption.…”
Section: How Bread-making May Change Fodmaps Levelmentioning
confidence: 99%
“…Another study has shown that low-FODMAPs rye breads, approximately 30% reduction of mannitol and fructans, caused less gastrointestinal symptoms, as abdominal pain, flatulence, stomach rum- and intestinal cramps ( Laatikainen et al, 2016 ). A third study conducted by Pirkola et al (2018) demonstrated that low-FODMAP rye bread leads to reduced colonic fermentation and flatulence severity when compared with regular rye bread consumption.…”
Section: How Bread-making May Change Fodmaps Levelmentioning
confidence: 99%
“…Hence, sourdough bread may be more suitable for some individuals with IBS than standard types of bread. A 2019 review found some evidence from small, low‐quality studies (seven studies) suggesting that sourdough bread may be better tolerated in both healthy individuals and those with gastrointestinal conditions (Dimidi et al 2019) and, in a small additional study ( n = 7), low FODMAP rye bread significantly reduced colonic fermentation compared with standard rye bread, though there was no significant difference in symptoms (Pirkola et al 2018). In addition to FODMAPs, some of the gluten in sourdough bread may be hydrolysed during fermentation, but not all and so while it is sometimes suggested that sourdough bread is more suitable for individuals with coeliac disease, this is in fact not the case.…”
Section: Future Trendsmentioning
confidence: 99%
“…The use of this zero FODMAP sourdough in low FODMAP rye bread making involves the addition of unfermented rye flour, which is fermented for only a short time [ 65 ]. Nevertheless, the choice of appropriate raw materials and the use of FruA-positive and mannitol-fermenting lactobacilli allows fructan degradation in rye and rye sourdoughs for the production of bread with a low content of fructans and mannitol but a comparable fiber content when compared to regular bread [ 66 , 67 , 68 ].…”
Section: Concepts For Low Fodmap Sourdough Bakingmentioning
confidence: 99%
“…Including the low FODMAP rye bread thus also increased the dietary fiber intake to the recommended level in IBS patients, avoiding drawbacks of the other low FODMAP diets [ 15 ]. A second randomized double-blind controlled crossover study evaluated the amount of breath hydrogen levels after consuming low FODMAP rye bread or regular rye bread [ 68 ]. Low FODMAP rye bread reduced the generation of hydrogen by colonic fermentation [ 68 ].…”
Section: Proof Of Concept From Clinical Trials With Low Fodmap Ryementioning
confidence: 99%
See 1 more Smart Citation